Synthesizing resilience: Key insights from a technical working group meeting - Kayamba-Phiri, Fundi (International Food Policy Research Institute, 2023)
Titukulane was designed to reduce the number of chronically food insecure households by enhancing the capacities of local and national governance structures to implement resilience-focused policies. To achieve this Titukulane is implementing interventions that build resilience and improve food security and nutrition outcomes for communities. Specifically, under Purpose area 3, these interventions are aimed at building institutional and local capacities to reduce risk and increase resilience among ultra-poor and chronically vulnerable households. Specific interventions implemented under Purpose 3 are disaster risk management, natural resource management and overall coordination of the National Resilience Strategy especially at district level.